Strategi Digital Branding pada Startup Social Crowdfunding (Studi Kasus pada Kitabisa.com) - Syahrul Hidayanto; Ishadi Soetopo Kartosapoetro (KOMUNIKATIF : Jurnal Ilmiah Komunikasi, 2020)
The era where information can be accessed quickly and flexibly presents its own challenges for startup branding in the crowdfunding sector. Kitabisa.com as the most popular crowdfunding platform in Indonesia certainly becomes an example in terms of digital branding strategies for other startups working in the same sector. This study aims to find out how digital branding strategies are in social crowdfunding startups in the industrial era 4.0. This study uses a qualitative approach in gaining a broad and deep understanding of digital branding strategies in social crowdfunding startups. The chosen research strategy is a case study. Based on the literature review that has been done, this research is the first in Indonesia that focuses on raising the theme of digital branding on social crowdfunding startups. The results show that Kitabisa.com has built its brand based on market insights, which contributes to its current success with a strong internal communication strategy along with consistent external communication. For brands to remain relevant and active, branding must be seen as an ongoing process that requires continuous adjustments through media monitoring and reacting to negative issues that can weaken the company's position.